Profiling of cholinesterase extracted from the brain tissue of Diodon hystrix and its inhibition reaction towards carbamates - Haris, Akid; Nordin, Noreen; Mustapa, Nur Azizah; Abd. Sani, Suraya; Shukor, Mohd Yunus; Sabullah, Mohd Khalizan (Universiti Putra Malaysia Press, 2020)
Diodon hystrix, commonly known as spot-fin porcupine fish is a salt-water fish belonging to the Diodontidae family. It is widely distributed in Sabah wet market due to its commercial value. This study exploits the effectiveness of Cholinesterase (ChE) obtained from the brain tissue of D. hystrix in detecting carbamates inhibitory activities. Carbamate pesticides known to inhibit ChE and toxic towards living organisms can contaminate the water bodies. By using diethylaminoethanol (DEAE) Sepharose ion exchange chromatography, a total of 40% recovery yield of ChE was obtained with a 165.77 purification fold. Furthermore, the ChE showed a high affinity towards acetylthiocholine iodide (ATC) with an optimum activity at pH 7.45 and temperature ranging from 20 to 40℃. Among five different types of carbamates, methomyl was found to have the highest percentage of inhibition analyzed using ChE inhibitory assay, followed by carbofuran, bendiocarb, carbaryl and propoxur with >85% inhibition rate. The results concluded that ChEs extracted from the brain tissue of D. hystrix are applicable to be used as a bioindicator in detecting the presence of carbamates.